Perancangan Aplikasi untuk Pengoptimalan Distribusi Barang Menggunakan Metode North West Corner (NWC) dan Stepping Stone Berbasis Web (Studi Kasus: Yumni Konveksi) - Anggit Prastika Setiany; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Yumni Konveksi is one of the convection businesses that producing school uniforms and distributing them to schools in several regions in Indonesia. The effective and efficient management of production processes, especially proper distribution, will provide a dominant contribution to the development progress of the business. As of the distribution management must be proper to be efficient because it will affect on distribution costs. A method to optimize the distribution costs is by using the transportation method. In transportation problems, in general, problem solving can be done in two phases, include: phase I by applying the North West Corner (NWC) method. While, the second phase is the final completion using the Stepping Stone method. Hence, a web-based application program is developed to solve the problem of distributing goods costs by implementing the North West Corner (NWC) method as an initial solution and the Stepping Stone method as the optimal solution to optimize the operational costs of distributing goods, school uniforms at Yumni Konveksi. The system development method used is the waterfall method. The system modeling in programing applications employs the Unified Modeling Language (UML) design. This application is made using the PHP programming language and MySQL in data-based management (database).